Effects of light intensity and co-inoculation of arbuscular mycorrhizal fungi and rhizobium on root growth and nodulation of Indigofera tinctoria - Maria Theresia Sri Budiastuti; Djoko Purnomo; Supriyono Supriyono; Bambang Pujiasmanto; Desy Setyaningrum (Universitas Sebelas Maret, 2020)
Indigofera tinctoria is a legume that is cultivated as a source of natural indigo dyes. As a legume, Indigofera tinctoria is capable of symbiosis with soil microbes. This study evaluates the effects of light intensity and microbial inoculation on root growth and nodulation. The study used a complete randomized block design with a split-plot pattern. Light intensity was the main plot with four levels of light intensity 100%, 50%, 25%, and 10%. Microbial inoculation was a subplot with four levels without inoculation, mycorrhizae inoculation, rhizobium inoculation, and double inoculation with both mycorrhizae and rhizobium. The results obtained show that light intensity and microbial inoculation affected root length, root fresh weight, root biomass, and the number of nodules. 50% light intensity was optimum for root length, while 100% light intensity was optimum for root fresh weight, root biomass, and a number of nodules. Root growth and nodulation were further increased with double inoculation. The combination of light intensity and microbial inoculation affected root biomass and nodulation. The combination of 100% light intensity and double inoculation resulted in the highest root biomass and nodule numbers. Mycorrhizae and rhizobium have a synergistic relationship to nodulation and root growth. Double inoculation with mycorrhizae and rhizobium efficiently increased root biomass and the number of nodules under low or high light intensity.